Mixed Psyllium Fiber Improves the Quality, Nutritional Value, Polyphenols and Antioxidant Activity of Rye Bread - Agata Wojciechowicz-Budzisz; Ewa Pejcz; Radosław Spychaj; Joanna Harasym (Foods, 2023)
The aim of the study was to determine the influence of the different shares (0/100, 5/95, 10/90 and 15/85 ratios) of a ground psyllium fiber (PF) mixture of 80% psyllium seeds (Plantago psyllium) and 20% psyllium husk (Plantago ovata Forsk) on the quality characteristics, chemical composition, total polyphenolic content (TPC), and antioxidant activity of rye bread (RB). The study was conducted with rye flour (RF) type 580 and 720 and two dough preparation methods (single-phase—1F, two-phase—2F). The inclusion of psyllium fiber in rye bread resulted in an increase in the overbaking of bread by 12.4%, total protein by 1.7%, ash by almost twofold, and TDF content by more than twofold. Psyllium fiber addition also led to a twofold improvement in antioxidant activity and an increase in TPC from 35.5 to 109.1 mg GAE/100 g d.m., as well as enhanced porosity of the crumb from 7.1 to 7.6 points on the Mohs scale. However, it caused a decrease in specific loaf volume by 10%, springiness by 3.5%, chewiness by almost 12%, and gumminess of the crumb by 8.1%. A darkening of the crust (reduction in the L* value by 10.7%) and crumb (reduction in the L* value by 37.6%) was observed as well. Notably, the results indicated that a 10% share of PF can be considered a potentially beneficial and functional ingredient, promoting health benefits without negatively affecting the physical and sensory qualities of rye bread. This suggests the potential use of PF for enhancing the nutritional value of RB without compromising its overall quality.